Shot peening of stainless steels and their monitoring via Barkhausen noise emission - M. Neslušan; P. Minárik; J. Čapek; T. Kmječ; Z. Florková; K. Zgútová; L. Trško (Journal of Materials Research and Technology)
This study investigates the shot peening of stainless steels with varying chemical compositions, focusing on the resulting microstructures and the associated Barkhausen noise emission. The response of the fully ferritic AISI 430 matrix to surface bombardment by small steel particles is compared to that of fully austenitic stainless steels, AISI 301 and AISI 316Ti. Furthermore, AISI 321 DF is utilised in this study as the matrix material, characterised by a mixed microstructure of austenite and ferrite resulting from its specific chemical composition—particularly the insufficient content of austenite-stabilising elements, such as nickel. The effects of shot peening are investigated as a function of varying numbers of shot peening cycles. The resulting surface condition is analysed in terms of topography, residual stress state, and microstructure, with particular emphasis on phase composition. Finally, Barkhausen noise emission is collected and expressed in terms of the aforementioned aspects. It was found that the Barkhausen noise in the fully ferritic AISI 430 is dropping down due to increasing dislocation density, whereas the Barkhausen noise in AISI 301, as well as AISI 3016Ti, is growing along the number of the shot peening cycles due to the increasing fraction of ferromagnetic strain-induced martensite produced in the paramagnetic austenite. This growth becomes stronger in AISI 301 due to the lower content of the austenite stabilisers. The initial growth of Barkhausen noise for AISI 321 DF for two cycles is followed by the progressive decrease along the rolling direction. However, due to remarkable microstructure anisotropy, the transversal direction exhibits initial growth followed by a saturation phase. Barkhausen noise in AISI 301 and AISI 3016Ti is mostly a function of the strain-induced martensite fraction, whereas the contribution of the stress state takes only a minor role.